Managerial competencies and innovations in the company – the case of enterprises in Poland - Szczepańska-Woszczyna, Katarzyna; Dacko-Pikiewicz, Zdzisława (Business, Management and Economics Engineering, 2014)
The determinants of the successful innovation implementation in the company include human capital and competencies of both managers and employees. In order for successful innovation management to occur, a manager must acquire or possess expertise in the domain at hand, as well as specific competencies. The paper has focused on the identification of the essential managerial competencies to promote and enhance innovation in companies. The study was conducted among managers of top, middle and operational management level in companies operating in Poland. It seems that competencies for each of the three group of managers have not been described in detail yet. The research has identified key competencies of managers in the context of implementing innovation in the company as well as differences resulting from the level of management in the organization. The research has helped to identify discrepancies between the current level of competencies needed to achieve organizational objectives, and the expected level ensuring maximum efficiency during their implementation.